Assessing bundles of ecosystem services from regional to landscape scale: insights from the French Alps. Issue 5 (31st July 2015) - Crouzat, Emilie; Mouchet, Maud; Turkelboom, Francis; Byczek, Coline; Meersmans, Jeroen; Berger, Frederic; Verkerk, Pieter Johannes; Lavorel, Sandra; Diekötter, Tim
Summary Assessments of ecosystem services (ES) and biodiversity (hereafter ecological parameters) provide a comprehensive view of the links between landscapes, ecosystem functioning and human well‐being. The investigation of consistent associations between ecological parameters, called bundles, and of their links to landscape composition and structure is essential to inform management and policy, yet it is still in its infancy. We mapped over the French Alps an unprecedented array of 18 ecological parameters (16 ES and two biodiversity parameters) and explored their co‐occurrence patterns underpinning the supply of multiple ecosystem services in landscapes. We followed a three‐step analytical framework to i) detect the ES and biodiversity associations relevant at regional scale, ii) identify the clusters supplying consistent bundles of ES at subregional scale and iii) explore the links between landscape heterogeneity and ecological parameter associations at landscape scale. We used successive correlation coefficients, overlap values and self‐organizing maps to characterize ecological bundles specific to given land cover types and geographical areas of varying biophysical characteristics and human uses at nested scales from regional to local. The joint analysis of land cover richness and ES gamma diversity demonstrated that local landscape heterogeneity alone did not imply compatibility across multiple ecosystem services, as some homogeneous landscape could supply multiple ecosystem services. Synthesis and applications. Bundles of ecosystem services and biodiversity parameters are shaped by the joint effects of biophysical characteristics and of human history. Due to spatial congruence and to underlying functional interdependencies, ecological parameters should be managed as bundles even when management targets specific objectives. Moreover, depending on the abiotic context, the supply of multiple ecosystem services can arise either from deliberate management in homogeneous landscapes or from spatial heterogeneity.